The role of ADAM10 in astrocytes: Implications for Alzheimer’s disease - Elsworthy, Richard J.; Hill, Eric J.; Dunleavy, Connor; Aldred, Sarah (Frontiers in Aging Neuroscience, 2022)
Much of the early research into AD relies on a neuron-centric view of the brain, however, evidence of multiple altered cellular interactions between glial cells and the vasculature early in AD has been demonstrated. As such, alterations in astrocyte function are widely recognised a contributing factor in the pathogenesis of AD. The processes by which astrocytes may be involved in AD make them an interesting target for therapeutic intervention, but in order for this to be most effective, there is a need for the specific mechanisms involving astrocyte dysfunction to be investigated. ‘α disintegrin and metalloproteinase’ 10 (ADAM10) is capable of proteolytic cleavage of the amyloid precursor protein which prevents amyloid-β generation. As such ADAM10 has been identified as an interesting enzyme in AD pathology. ADAM10 is also known to play a role in a significant number of cellular processes, most notable in notch signalling and in inflammatory processes. There is a growing research base for the involvement of ADAM10 in regulating astrocytic function, primarily from an immune perspective. This review aims to bring together available evidence for ADAM10 activity in astrocytes, and how this relates to AD pathology.